1010 Audit of Acute Management of Sudden Onset Sensorineural Hearing Loss and Streamlining of Local Management Pathway. (19th August 2022) - Kruczynska, A; Cordiner, P; Maini, S
Abstract: Aim: Sudden onset sensorineural hearing loss (SSNHL) presents infrequently to ENT services in Aberdeen Royal Infirmary. Although ENT UK guidelines are in place for the management of SSNHL, the practicalities of organising these cases within our department can be challenging to junior staff leading to variation in time to review and timings of intervention. We Aimed to assessed current local practice in comparison compare it to national ENT UK guidelines Method: Retrospective audit of 6 months data set recording management pathway of patients presenting with SSNHL to Rapid Access Clinic of Royal Aberdeen Infirmary Hospital. Electronic patient records were searched for: time of referral, duration of symptoms, times to first ENT review, intervention and audiogram, and timings and management during subsequent reviews. Results: Seven patients meeting the inclusion criteria were identified and included in the audit. Average times from referral were calculated including time from referral to intervention (1.47 days), from referral to first ENT review (3.82 days), from referral to first audiogram (4.43 says). Average time from presentation to starting oral steroids was very efficient of just 0.33 days and average time from symptom onset to oral steroids initiation was 7.5 days suggesting late patient presentation. Conclusions: The data gather helped our department to reinforce management pathway of SSNHL as per ENT UK guidelines and improved the way urgent audiograms are organised in the hospital. It also emphasised the importance of performing tuning fork test to determine the nature of hearing loss when audiogram is not immediately available.